Pembangunan Zona Integritas Dalam Mewujudukan Kualitas Pelayanan Publik di Polres Cilegon - Revani Gena Azzunaika; Kandung Sapto Nugroho; Rina Yulianti (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
The phenomenon of corrupt behavior is already worrying and threatens the sustainability of life, especially the Polri bureaucracy. Efforts to overcome corruption in the bureaucracy as a bureaucratic reform policy through the Integrity Zone (ZI) development program, one of which was carried out by the National Police. The aim of this research is to examine the development of the Integrity Zone which has received the title of WBK (Corruption-Free Area) at the Cilegon Police Headquarters. The method used is a qualitative approach. Data collection through observation, interviews and documentation. The results of the study found that the total ZI weight score at the Cilegon Polres fulfilled the WBK predicate which reached 93.56 scores. The lowest weighted value of the lever element is the aspect of management and strengthening of supervision. The highest score is in the aspect of strengthening accountability and improving service quality. The ZI innovation carried out at the Cilegon Police in building WBK is by improving public services that are comfortable and easily accessible to the public by providing an Integrated Service Center (Pusyandu), where several types of public services are carried out such as SKCK attendants, crowd permits and STTP, STM and Wasendak. Obstacles in the development of ZI at the Cilegon Polres include the lack of budget availability in encouraging the development of ZI, the lack of understanding of the HR apparatus between units from each section and units within the Cilegon Polres environment. Obstacles to the readiness of the lack of a public service activity publication team, many application systems that become services that cannot be used such as BPKB/police ticket service, intelligence services, and SPKT services.